Indie-(an) Music: An Ethnography of a Rock Music Venue in Delhi. (3rd February 2015) - Cashman, David
Abstract : Local English-language adaptations of western rock are performed in India primarily for consumption by young, western-influenced, and English-speaking middle-class Indians. As Indian rock is predominantly a live rather than a recorded practice, venues are of particular import within the Indian rock scene. However, little formal research upon live Indian popular music has been undertaken. Between September and December 2013, the author undertook research in Delhi investigating live popular music. This article uses an ethnographic approach to investigate and contextualise the music-culture of a music venue, Café 27, within the Indian rock scene in Delhi. The article finds that the venue in question has a two-fold purpose: it provides a space for performance of local adaptations of popular music genres permitting Delhi-ite musicians to earn a living, and it provides a space for the western-influenced middle- and upper-classes to define their identity.